Comparative Study of Platinum(II) and Platinum(IV) Complexes with 2‐(Pyridin‐2‐ylmethylamino)acetic Acid and 4‐(Pyridin‐2‐ylmethylamino)benzoic Acid: Experimental and Theoretical Analysis - Stefan Richter; Dušan Dimić; Peter Lönnecke; Goran N. Kaluđerović; Evamarie Hey‐Hawkins (ChemistryEurope, 2025)
The coordination behavior of 2‐(2‐pyridin‐2‐ylmethylamino)acetic acid (HL1) and 4‐(2‐pyridin‐2‐ylmethylamino)benzoic acid (HL2) toward PtII and PtIV is investigated. While the corresponding carboxylato complexes are obtained with HL1 (N,N,O coordination of L1−, elimination of HCl; 1a and 1b), only N,N coordination of HL2 which still features the carboxylic acid group is observed (2a and 2b). Thus, complexes 2a and 2b would be suitable for subsequent conjugation to biomolecules using the free COOH group. On heating in air, the ligand in 2a is oxidized (formal elimination of dihydrogen) to give the imine complex 3a, which could also be obtained directly from the corresponding ligand HL3 ((Z)‐4‐(pyridin‐2‐ylmethyleneamino)benzoic acid). The obtained complexes are characterized by 1H, 13C{1H} NMR and IR spectroscopy, elemental analysis, and, in the case of complexes 1a, 1b, and 3a, also by single‐crystal X‐ray crystallography. In addition, quantum chemical calculations are carried out to gain deeper insights into the molecular structures and properties of both the complexes and their precursor ligands. A comparative study showed that the theoretical calculations are in good agreement with the experimental findings. This combined experimental and theoretical approach facilitated a comprehensive understanding of the coordination behavior and structural features of the investigated complexes.